2009
DOI: 10.1590/s1414-32832009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Gestão participativa e corresponsabilidade em saúde: limites e possibilidades no âmbito da Estratégia de Saúde da Família

Abstract: De acordo com a Política Nacional de Humanização do SUS - HumanizaSUS - a gestão participativa implica o envolvimento dos trabalhadores da saúde, gestores e usuários em um pacto de corresponsabilidade baseado em contratos e compromissos com o sistema de saúde. Este artigo discute limites e possibilidades de incorporação da gestão participativa e incorporação do princípio da corresponsabilidade no âmbito da Estratégia Saúde da Família (ESF). Foi desenvolvido um estudo de casos múltiplos, integrando estratégias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
(10 reference statements)
0
8
0
14
Order By: Relevance
“…19 The use of combined methods was also noted: interviews and documental sources, 38 interviews and participative observation, 1,17,26,34,35,44,e questionnaire and focus groups. [45][46][47] The majority of analyses used were content analysis, 5,12,16,20,26,30,35,44,45,47,g followed by thematic analysis. 4,6,18,37,42 Other strategies such as descriptive analysis, 41 discourse analysis, 22,29 dialectical hermeneutics and ethnography 25,40 were used to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The use of combined methods was also noted: interviews and documental sources, 38 interviews and participative observation, 1,17,26,34,35,44,e questionnaire and focus groups. [45][46][47] The majority of analyses used were content analysis, 5,12,16,20,26,30,35,44,45,47,g followed by thematic analysis. 4,6,18,37,42 Other strategies such as descriptive analysis, 41 discourse analysis, 22,29 dialectical hermeneutics and ethnography 25,40 were used to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%
“…2,23,26,44 However, as one study indicated, the process of taking responsibility within the scope of health care and management is fairly incipient in primary care. 45 A recurring topic was the pack of a professional profile, identified as an element which made humanized care difficult. Concerning the lack of health care professionals prepared to act in a humanized way, studies considered that investment in ongoing professional development and education is necessary.…”
mentioning
confidence: 99%
“…It is worth remembering that the degree of democratization of the internal environment of the institutions 18 must be considered in the analysis of the participative management.…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, estudos mostram que, apesar dos avanços, a participação da população no cotidiano dos serviços pouco tem influenciado na sua organização e na formulação de projetos e ações atrelados às necessidades da comunidade 23,24 . Outros autores encontraram uma carên-cia de iniciativas para o planejamento das ações de saúde, resultando em um processo de trabalho parcelar, pouco reflexivo e ancorado na resolução de problemas imediatos surgidos principalmente do contato da equipe com os usuários que demandam por atendimentos clínicos não programados 25,26,27,28 .…”
Section: Introductionunclassified